2019
DOI: 10.2319/031819-219.1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Maxillary Expansion in Children with Nocturnal Enuresis: A Randomized Placebo-controlled trial

Abstract: Objective: To investigate whether rapid maxillary expansion (RME) is a useful treatment method for nocturnal enuresis (NE) and whether the treatment effect is due to placebo. The study also aimed to identify prognostic variables in patients responding to treatment. Materials and Methods: Thirty-eight children with therapy-resistant NE were recruited and randomized into two groups: the intervention group or placebo group. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 20 publications
0
26
1
Order By: Relevance
“…In general, the selected articles were published between 1990 and 2020 in medical and dental journals and consisted of seven non-randomized prospective studies [10][11][12][13][25][26][27] and one randomized controlled trial. 28 The sample sizes of the studies were quite variable, and only one article 13 showed control group composed of untreated patients. The patients were either in the mixed or early permanent dentitions.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, the selected articles were published between 1990 and 2020 in medical and dental journals and consisted of seven non-randomized prospective studies [10][11][12][13][25][26][27] and one randomized controlled trial. 28 The sample sizes of the studies were quite variable, and only one article 13 showed control group composed of untreated patients. The patients were either in the mixed or early permanent dentitions.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[12][13][14][28][29][30] The amount of expansion obtained ranged from 4 mm 25 to 8.2 mm, 13 and the reduction of NE episodes was analyzed in both the short (6 months 28 and 8 months 25 ) and the long term (13 months, 26,27 36 months, 12,13 48 months, 10 and 120 months 11 ) by means of questionnaires, [11][12][13] interviews with patients' parents, 10,[25][26][27] registration of NE episodes on a voiding chart, 28 registration of daytime voided volumes and nocturnal urine production via weighing of diapers or sheet covers, 28 polysomnography examinations, 27 and laboratory tests of osmolality of the blood plasma to quantify the level of ADH. 12 Finally, participants of all studies were diagnosed with at least one of the following respiratory disorders: mouth breathing, 10,11,13,25,28 mixed breathing, 25 respiratory tract infections, 13 snoring, 13,26,28 adenoid hypertrophy, 10,24 amygdala hypertrophy, 10,13,25 nasal septum deviation, 25 and/or nasal obstruction. [25][26]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 and 3 show the risk of bias judgement for the final studies with the tools used and a justification for the grade given for each study. Two of the three CCTs [23][24][25] were assessed at moderate risk of bias and one at serious risk of bias [27], whereas the RCT [26] was assessed to be at low risk of bias.…”
Section: Samples and Interventionmentioning
confidence: 99%